2001
DOI: 10.1128/aem.67.4.1663-1674.2001
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Diversity of Bacterial and Archaeal Communities in the Anoxic Zone of the Cariaco Basin

Abstract: Microbial community samples were collected from the anoxic zone of the Cariaco Basin at depths of 320, 500, and 1,310 m on a November 1996 cruise and were used to construct 16S ribosomal DNA libraries. Of 60 nonchimeric sequences in the 320-m library, 56 belonged to the subdivision of the Proteobacteria (-Proteobacteria) and 53 were closely related to ectosymbionts of Rimicaris exoculata and Alvinella pompejana, which are referred to here as epsilon symbiont relatives (ESR). The 500-m library contained sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
194
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(209 citation statements)
references
References 52 publications
14
194
1
Order By: Relevance
“…Under sulfatereducing conditions with 13 C-labeled acetate, Arcobacter became enriched fast and although the authors suggested that Arcobacter was involved in sulfur cycling, iron and manganese reduction during the sediment incubations were indicated by increasing concentrations of dissolved manganese and iron (Webster et al, 2010). Arcobacter-related sequences have been found in clone libraries of many marine and terrestrial habitats (Campbell et al, 2006), for example, Arctic and Antarctic surface sediments and the anoxic water column of the Cariaco Basin, the Black Sea, the African shelf and an anoxic fjord (Nitinat Lake) (Madrid et al, 2001;Bowman and McCuaig, 2003;Vetriani et al, 2003;Lavik et al, 2009;Schmidtova et al, 2009). The metabolism of these organisms in the anoxic water columns is somewhat uncertain but sulfide oxidation has been repeatedly suggested (Lin et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Under sulfatereducing conditions with 13 C-labeled acetate, Arcobacter became enriched fast and although the authors suggested that Arcobacter was involved in sulfur cycling, iron and manganese reduction during the sediment incubations were indicated by increasing concentrations of dissolved manganese and iron (Webster et al, 2010). Arcobacter-related sequences have been found in clone libraries of many marine and terrestrial habitats (Campbell et al, 2006), for example, Arctic and Antarctic surface sediments and the anoxic water column of the Cariaco Basin, the Black Sea, the African shelf and an anoxic fjord (Nitinat Lake) (Madrid et al, 2001;Bowman and McCuaig, 2003;Vetriani et al, 2003;Lavik et al, 2009;Schmidtova et al, 2009). The metabolism of these organisms in the anoxic water columns is somewhat uncertain but sulfide oxidation has been repeatedly suggested (Lin et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The Thiovulum subgroup is a phylogenetic group that includes several sulfur-oxidizing bacteria, such as Thiomicrospira denitrificans (isolated from marine mud; Timmer-ten Hoor, 1975) and Thiomicrospira sp. strain CVO (isolated from the production water of an oil well; Gevertz et al, 2000), and many environmental clones of 16S rRNA genes (obtained from hydrothermal vents; Corre et al, 2001;Moyer et al, 1995), marine sediments (Madrid et al, 2001) and cave springs (Engel et al, 2003). Later, a bacterial strain (strain YK-1 T ) that represented the cluster-1 bacteria was isolated and physiologically characterized (Kodama & Watanabe, 2003).…”
mentioning
confidence: 99%
“…for 2-4 days. Genomic DNA was purified from the liquid cultures using the protocol of Fujimoto et al (2004) and the DNA templates were used to obtain partial 16S rRNA gene sequences by PCR with primers 344F (59-ACGGGGCGCAGCAGGCGCGA-39) and 1492R (59-GGCTACCTTGTTACGACTT-39); numbers of primers refer to positions relative to the Escherichia coli 16S rRNA gene (Madrid et al, 2001). When the isolated colonies were confirmed as methanogens by 16S rRNA gene sequencing, the liquid cultures maintained at 4 u C were serially diluted in JCM 530 medium and streak plated again, in the Coy anaerobic chamber.…”
mentioning
confidence: 99%